Mengungkap Jerat Hukum Pelaku Kekerasan Seksual Analisis Kritis UU No. 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual - Najmudin, Nandang; Adinda, Nendena Rizqi; Toisuta, Usman Abdul Jihad; Huda, Tamimil (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This study aims to critically and legally analyze the concept of criminal liability for perpetrators of sexual violence and identify the advantages and challenges of implementing Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (TPKS Law). The background to the problem is driven by the failure of previous regulations (the Criminal Code) to cover the various modes of operation of TPKS and provide comprehensive protection for victims. This study uses a normative legal research method with a statute approach and a conceptual approach. Primary legal materials (TPKS Law) and secondary materials (criminal law doctrine and scientific journals) were analyzed qualitatively and descriptively to examine the formulation of offenses, the punishment system, and the victim-centered approach philosophy contained therein. The results of the study show that the TPKS Law has become a significant milestone in criminal law reform through the expansion of strafbaarfeit. This law has successfully closed the criminalization gap by criminalizing eight new types of TPKS, including Non-Physical Sexual Harassment and Electronic-Based Sexual Violence (KSBE), whose definitions emphasize the absence of consent and power relations. In addition, the TPKS Law expands the subjects of law that can be held accountable to include corporations and introduces progressive additional penalties, such as the obligation of restitution and disclosure of the perpetrator's identity, as well as strictly limiting the use of restorative justice mechanisms in serious cases. Although innovative, the effectiveness of the legal provisions in the TPKS Law still faces serious implementation challenges, particularly regarding the issue of proving non-physical/electronic crimes and the gap between legal certainty of punishment and the fulfillment of restorative justice for victims. Therefore, it is recommended that the government immediately strengthen the technical readiness of law enforcement officials and allocate adequate resources for integrated service infrastructure and restitution enforcement mechanisms at the regional level to ensure the successful implementation of a victim-centered legal paradigm.